Yields of relay cropped greens grown in green roof production systems - Leigh Whittinghill; Pradip Poudel (Urban Food Systems Symposium, 2020)
As interest in urban food production increases, urban farmers are looking for solutions to the challenge of space availability. One solution is to move production to building rooftops, a space that is often underutilized. The use of green roof technology is one method of achieving food production on rooftops; however, there are some additional challenges associated with this practice as a result of the fast-draining, low-nutrient media used. This is particularly challenging for vegetable crops, which typically require more nutrients than the ornamental plants traditionally grown in green roof media. Some rooftop farmers are adding additional organic matter in the form of compost to their beds as an alternative to chemical fertilizers. Currently, there is little research on how rooftop production systems affect crops. Green roof platforms were established at the Harold R. Benson Research and Demonstration Farm in Frankfort, Kentucky, to examine crop yield in green roof systems supplemented with compost. Treatments were a topsoil no compost control, a green roof media no compost control and 3 green roof media treatments: the addition of 0.33, 0.66, or 1 kg m-2 of compost. Organic fertilizers were used to supply additional nutrients to vegetable plants. The crops selected were lettuce, arugula, mizuna, mustard, Swiss chard, kale, and spinach. These were relay cropped in succession during two growing seasons (2018 and 2019). At each harvest, the amount of time harvesting required (in seconds), total yield, and marketable yield (determined by visual examination) were measured for each platform. Yield results were analyzed in R. Analysis of variance was performed on all variables for each crop; compost treatment and year were fixed effects. Significant differences between treatment means were analyzed using Tukey HSD (alpha of 0.05). Results for kale show differences between 2018 and 2019 for harvest time and total yield in the topsoil control, but no differences for marketable yield. These differences are likely due to weather conditions. Kale harvest time, total yield in 2019 but not 2018, and marketable yield were highest in the topsoil control. Harvest time of the topsoil control was not significantly higher than the 1 kg m-2 of compost in green roof media. The marketable yield of the topsoil control was not significantly higher than 0.66 or 1 kg m-2 compost treatments in green roof media. Results for additional crops will also be presented.
Keywords: urban agriculture; soilless media; compost; lettuce; spinach; kale